Cross-Sectional Identification of Private Information - Bongaerts, Dion; Rösch, Dominik; van Dijk, Mathijs (The Review of Asset Pricing Studies, 2026)
Abstract We propose a new private information measure based on a model of strategic trade optimization in the cross section of securities. Investors receive liquidity and private information shocks and optimize trading across securities, accounting for price impact (Kyle’s λ). The model yields a simple private information measure: λ×OIB (order imbalance). Intuitively, order imbalance is more likely to be information-driven when trading is expensive. We validate our measure by showing that it is greater for smaller firms with higher analyst dispersion, peaks with insider trades, helps explain return reversals, predicts return volatility, and increases before M&A announcements and after analyst coverage terminations. (JEL G11, G12, G14)